Dissipativity Analysis of Switched Gene Regulatory Networks Actuated by Persistent Dwell-Time Switching Strategy - Shen, Hao; Huang, Zhengguo; Xia, Jianwei; Cao, Jinde; Park, Ju H. (IEEE transactions on systems, man, and cybernetics. Systems, 2021)
This article concentrates on the global uniform exponential stability analysis and dissipativity property for a class of discrete-time gene regulatory networks (GRNs). To describe the processes at work as cells change phenotype, the time-dependent persistent dwell-time switching strategy is applied to switched GRNs. Formulating the mode-dependent Lyapunov-Krasovskii functional, the global uniform exponential stability and strictly dissipativity property criteria for the GRNs subject to time-varying delays are presented. Ultimately, an example, including three cases is employed to illustrate and discuss the availability of the given criteria.